Incidentes relacionados a medicamentos em um ambulatório de quimioterapia - Carollo, Jéssica Baldissera (2017)
Among the incidents in health care, those related to medications are becoming increasingly frequent in Brazilian institutions. The present study aimed to identify drug-related incidents in a chemotherapy clinic of an university’s hospital. Study, descriptive, with the monitoring of patients seen in the chemotherapy clinic of the Hospital Universitario de Santa Maria, between June to August 2016. For data collection, we used a research tool divided into four blocks. Block A covers issues related to patient characterization. Block B contains issues related to medical prescription. Block C contains an issue related to the dispensing of drugs and the D block issues related to drug administration. The data was organized in Statistical Package for the Social Sciences (SPSS) 17.0 for Windows 8. 1403 medical records were accessed. Of these, 58.4% of the patients were female, aged between 53 and 65 years old with an average age of 57.6 years old. The results were presented based on the monitoring of 1403 patients seen in chemotherapy clinic, in which were analyzed the prescription, dispensing of drugs and their administration by the nursing staff. The findings were: 80% of the medical prescriptions were computerized, 91.9% of the patients were correctly identified in the prescription, 66.4% of the prescriptions had the prescriber identification, 95.7% of the prescriptions had the correct date, 86.2% of the prescriptions presented legible handwriting, 96.2% of the prescriptions presented abbreviations of the drugs, dose or posology, 65.8% of the prescriptions presented drugs with similar names, 85% of the prescriptions correctly expressed the dose, 98.4% of the prescriptions did not show if the patient was allergic to any medication, 99.1% of the prescriptions described the dose of the medication, 62.3% of the prescriptions presented the correct duration of the treatment, 83.3% of the prescriptions presented the dosage of the medications, 97.1% of the prescriptions presented the dilution of the medication, 95.2% of the prescriptions presented the time of infusion for a certain medication, 98.5% of the prescriptions described the route of administration for the medication. Regarding to the dispensing of the drugs, 98.5% of them were dispensed correctly. In 99.4%, medication administration was recorded by nursing, and 1.3% of the patients presented adverse reactions to the administered drugs. The incidents that caused damages in patients presented a rate of 0.4%. The average number of incidents per procedure was 3.6. In conclusion, this investigation presented relevant data on the reality of HUSM towards the incidents with drugs in a chemotherapy clinic. Therefore, based on these results, it is expected a contribution to the nurses' work regarding their daily practice and theoretical knowledge in order to minimize errors and promote patient safety.